Pengaruh Jenis, Spesialisasi Industri Auditor, Audittenure, Ukuran Perusahaan terhadap Going Concern Reporting - I Wayan Karman (Pusat P2M Politeknik Negeri Batam, 2017)
Auditor has responsibility to reveal the continuity of business entity on his opinion. There are two type of errors in the going concern audit opinion, that type 1 error and type 2 error. The purpose of this research is to provide empirical evidences of the influence of auditor type, auditor industrial specialitation, audit tenure, and company size on going concern reporting accuracy, which is measured by Type 2 error. Type 2 error accours when the auditor issues non-going concern audit opinion to company which bankrupt. Audit report is accurate, if the company goes survive after receiving non-going concern audit opinion. Bankruptcy is proxied by Altman Z Score. Population of this research is manufactur companies listed on Indonesian Stock Exchange in 2014 and 2015. This research uses 97 companies that meet the criteria of data observation. Companies were observed and sampled is 194 time series cross section data. Data were analyzed by binary logistic regression. The result of this research showan empirical evidences that auditor type has positive effect on going concern reporting accuracy, auditor industrial specialitation and audit tenure do not have effect on going concern reporting accuracy, company size has negative effect on going concern reporting accuracy.